A Pragma-Dialectical Analysis of Chinese Government’s Argumentation: A Case of ‘Comment on Country Report of Human Rights Practice by the U.S. Department of State’ - Ruhua, Jin (Sinología hispánica. China Studies Review, 2016)
This paper, adopting pragma-dialectical approach, analyses the Chinese government’s argumentative discourse in response to the accusation of its human rights practices by American government, in order to explore the former’s argumentation in resistance to America’s hegemony. It takes “Comment on Country Report of Human Rights Practices by the U.S. Department of State”, three pieces of official documents issued by Information Office of State Council of China (“IOSC”) from 1995 to 1997, as the research texts. It analyses the claim (standpoint), argument (reason), argument structure and scheme to find out the argumentative strategies of IOSC in these four aspects. It was found that: 1) in terms of standpoint, IOSC denied the view of U.S. side that China had human rights abuses in some parts of its Country Report; 2) in terms of argument, IOSC mainly provided four types of reasons: the U.S. counterpart distorted China’s domestic human rights practices in some cases, neglected the progress of human rights the Chinese government had made, took a blind eye to America’s own severe human rights violations, and American government’s accusation through Country Report was the embodiment of hegemony; 3) As to the argument structure, the Chinese government adopted non-mixed complex argumentation with their various types of multiple, coordinate and subordinate structure in combination on human rights issue; 4) in terms of argument scheme, IOSC mainly adopted symptomatic scheme in its discourse. The study provides practical values for the improvement of a development country’s international human rights discourse in the argumentative lens.